Die Jüdische Presse. - Hildesheimer, Hirsch; Mizrachi (Berlin : J. Benzian, 1923)
"Jüdische Presse" was an Orthodox German weekly that was founded in 1870 by Samuel Enoch and Azriel Hildesheimer, a prominent figure in the Orthodox community. The "Jüdische Presse" discouraged Orthodox Jews from withdrawing from the general Jewish community, similar to Hildesheimer's own views that cooperation among the Jewish communities helped combat antisemitism. It was one of the first papers to support the colonization of Palastine, although it was critical of Herzl and political Zionism. In 1919 it became the vehicle of the German Mizrachi, adding a section in Hebrew and Yiddish to its publication. (Source: "Juedische Presse" and "Azriel Hildesheimer," Encyclopaedia Judaica. accessed online 7/3/2013).
Subtitle varies.
Editor, 1883- Hirsch Hildesheimer.
Issues for <1920>-1923 have also title in Yiddish: Yudishe prese.
Description based on: 3. Jahrg., Nr. 1 (den 5. Jan. 1872); title from caption.
"Organ für die religiösen Interessen des Judentums."
Mode of access: Internet.
Keywords: Zionism -- Germany -- Periodicals; Judaism -- Germany -- Periodicals; Jews -- Germany -- Periodicals; Périodiques.; Periodicals; Periodicals; periodicals; Periodical